2015
DOI: 10.1210/en.2014-1961
|View full text |Cite
|
Sign up to set email alerts
|

A Stereological Analysis of NPY, POMC, Orexin, GFAP Astrocyte, and Iba1 Microglia Cell Number and Volume in Diet-Induced Obese Male Mice

Abstract: The hypothalamic arcuate nucleus (ARC) contains 2 key neural populations, neuropeptide Y (NPY) and proopiomelanocortin (POMC), and, together with orexin neurons in the lateral hypothalamus, plays an integral role in energy homeostasis. However, no studies have examined total neuronal number and volume after high-fat diet (HFD) exposure using sophisticated stereology. We used design-based stereology to estimate NPY and POMC neuronal number and volume, as well as glial fibrillary acidic protein (astrocyte marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 55 publications
(61 reference statements)
5
39
0
2
Order By: Relevance
“…Conversely, neuronal peroxisome proliferator–activated receptor-δ and growth hormone receptor knockout mice are resistant to HFD-induced hypothalamic inflammation and gliosis yet more susceptible to DIO than wild-type controls (71). Finally, a stereological analysis of the hypothalamus in HFD-fed mice revealed minimal evidence of neuronal loss and sustained gliosis though the diet composition and duration were different than prior studies (72•). Thus, the evidence supporting a direct role of hypothalamic inflammation and gliosis in promoting weight gain is clearly mixed.…”
Section: Conflicting Datamentioning
confidence: 64%
“…Conversely, neuronal peroxisome proliferator–activated receptor-δ and growth hormone receptor knockout mice are resistant to HFD-induced hypothalamic inflammation and gliosis yet more susceptible to DIO than wild-type controls (71). Finally, a stereological analysis of the hypothalamus in HFD-fed mice revealed minimal evidence of neuronal loss and sustained gliosis though the diet composition and duration were different than prior studies (72•). Thus, the evidence supporting a direct role of hypothalamic inflammation and gliosis in promoting weight gain is clearly mixed.…”
Section: Conflicting Datamentioning
confidence: 64%
“…The consumption of a HFD activates microglia and the expression of inflammatory cytokines in the hypothalamus, thereby disrupting the hypothalamic neuronal routes that maintain energy homeostasis [8,16]. We observed that the inflammatory effects of HFD were rapid, appearing in the nodose ganglion and hypothalamus one day after exposure to a HFD.…”
Section: Discussionmentioning
confidence: 84%
“…Earlier studies quantifying POMC neurons by β-endorphin immunohistochemistry (Huo et al 2006) or using mice expressing green fluorescent protein (GFP) under the POMC promoter (Cowley et al 2001) have reported around 3000–3500 POMC neurons in rodent ARC. However, a recent report quantifying POMC neurons using an antibody specific to the POMC precursor, estimated around 9000 immunoreactive cells (Lemus et al 2015). On the other hand, the number of NPY/AgRP neurons was estimated to be between 8000 and 10,000 (Betley et al 2013, Lemus et al 2015), analyzed using mice expressing GFP in an AgRP promoter-dependent manner.…”
Section: Neuroanatomy Of the Central Melanocortin Systemmentioning
confidence: 99%
“…However, a recent report quantifying POMC neurons using an antibody specific to the POMC precursor, estimated around 9000 immunoreactive cells (Lemus et al 2015). On the other hand, the number of NPY/AgRP neurons was estimated to be between 8000 and 10,000 (Betley et al 2013, Lemus et al 2015), analyzed using mice expressing GFP in an AgRP promoter-dependent manner.…”
Section: Neuroanatomy Of the Central Melanocortin Systemmentioning
confidence: 99%